2020
DOI: 10.1017/s1092852920001479
|View full text |Cite
|
Sign up to set email alerts
|

Substance-related exogenous psychosis: a postmodern syndrome

Abstract: There is growing recognition that substance use is associated with the emergence of psychosis.Elements of post-modernity dominate contemporary social contexts and operate as existential background factors that contribute to the emergence of substance-related psychotic phenomena, particularly use of potent and highly rewarding novel psychoactive substances (NPS). About 25% of first-episode psychoses are substance-induced (SIP). DSM-5 SIP diagnosis is based on the assumption that symptoms are transient and disap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 83 publications
2
71
0
3
Order By: Relevance
“…Therapeutically used drugs such as non-opioid analgesics, methylphenidate, and opioids were estimated to be on the whole to be the least harmful at present. Such relative safety perception however is certainly subject to change should misuse and abuse patterns change over time (45).…”
Section: Resultsmentioning
confidence: 99%
“…Therapeutically used drugs such as non-opioid analgesics, methylphenidate, and opioids were estimated to be on the whole to be the least harmful at present. Such relative safety perception however is certainly subject to change should misuse and abuse patterns change over time (45).…”
Section: Resultsmentioning
confidence: 99%
“…(46%) declared to have used a substance without knowing what it was at least once in their life. These results will be described in a separate manuscript (31). In our sample, 37 patients (40%) disclosed a lifetime misuse of prescription drugs.…”
Section: Resultsmentioning
confidence: 62%
“…Their effects and related risks are often unknown to both users and health professionals, due to the scarcity of evidence-based information regarding their toxicological profiles and to the ever-changing nature of this market (7,(26)(27)(28). Nevertheless, growing evidence reported potential acute and chronic psychiatric risks associated to NPS consumption, including confusion; paranoid thoughts; auditory and visual hallucinations; dissociation; delusions of reference, persecution, grandeur, and jealousy; cognitive impairment; hypomanic states; aggressiveness and irritability; violence; and suicidal thoughts (8,(29)(30)(31).…”
Section: Introductionmentioning
confidence: 99%
“…The delusions reported are similar to paraphrenic delusions, with a feeling of unreality, while the ability to analyze the feeling is preserved. In this regard, the model of the Lysergic Psychoma could be an interesting proposal (14). As already highlighted by previous studies (47), relevant symptoms were also inherent to the sphere of affectivity, both in the direction of positive and negative polarity.…”
Section: Discussionmentioning
confidence: 76%
“…Nevertheless, growing evidence supports the possibility of significant psychiatric and physical consequences related to NPS consumption ( 13 , 14 ). Recently, researchers have reported that NPS consumption may be associated with the onset of a variety of psychiatric symptoms and conditions, including confusion, paranoid thoughts, auditory and visual hallucinations, dissociation (e.g., derealization and somatopsychic depersonalization), insomnia, chronic cognitive impairment and delusions of reference, persecution, grandeur and jealousy, as well as hypomanic states, aggressiveness and irritability, violence, and suicidal thoughts ( 15 17 ).…”
Section: Introductionmentioning
confidence: 99%